Creating a Computing Programs Package to Aid in the Assessment and Prognosis of Patients Suffering from Cerebrovascular Diseases - Carlos Jaime Geroy Gómez; Rubén Bembibre Taboada; Darian Alvarez Rodriguez; Miguel Angel Buergo Zuaznábar; Diosdania Alfonso Falcón (Medisur)
Fundament: The have an evaluation and prognosis of patients suffering from cerebrovascular diseases in its acute phase is important in order to define the medical management as well as others several aspects. Objective: To create computing programs package to aid in the assessment and prognosis of patients suffering from cerebrovascular diseases. Method: A research and development study to create a package of programs using a C chart computing language (NET language) with recognized international scale compendium and the Cuban scale prognosis. Results: A Software which shows in different screens the correspondent variables to the different evaluative scales and the prognosis Cuban scale ¨Stroke¨ is created. It is applicable to every type of patient suffering from cardiovascular diseases and an immediate assessment and prognosis is obtained. It also has a data base. It is applicable in all ictus units of our country and abroad. Conclusions: A unique software was created as a valuable tool to the attention of patients suffering from cardiovascular diseases which permit to obtain a better assessment and prognosis of this kind of patient.